2022
DOI: 10.3390/foods11152314
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Evaluation of Ozone Water Combined with Ultrasound Cleaning on Crayfish (Procambarus clarkii)

Abstract: The effects of ozone water (OW) and ultrasound cleaning (UL) on microbial community diversity of crayfish were studied through microbial viable count and 16S rRNA gene sequencing. The results showed that compared with the control (CK), the ozone water combined with ultrasound cleaning (OCU) showed a significant reduction (p < 0.05) in total viable count (TVC), psychrophilic viable count (PVC), mesophilic viable count (MVC), Pseudomonas, hydrogen sulfide-producing bacteria (HSPB), molds and yeasts. Concretel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 59 publications
2
3
0
Order By: Relevance
“…Moreover, a* values of US and UP groups increased more rapidly than that of the control group, implying that US treatment accelerated the increase of redness. Consistent with the current study, Ling et al [26] observed the acceleration effect of US treatments on the increase of redness towards crayfish. It might be attributed to the mechanical effects of US treatment on the crayfish samples, which resulted in cytochrome release.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Moreover, a* values of US and UP groups increased more rapidly than that of the control group, implying that US treatment accelerated the increase of redness. Consistent with the current study, Ling et al [26] observed the acceleration effect of US treatments on the increase of redness towards crayfish. It might be attributed to the mechanical effects of US treatment on the crayfish samples, which resulted in cytochrome release.…”
Section: Resultssupporting
confidence: 92%
“…For the control group, the initial L*, a* and b* value of crayfish was 42.27, 5.81 and 2.23, respectively. Similar color coordinates of crayfish were reported previously [26] .…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations